2014
DOI: 10.3389/fmicb.2014.00595
|View full text |Cite
|
Sign up to set email alerts
|

Induction and maintenance of DNA methylation in plant promoter sequences by apple latent spherical virus-induced transcriptional gene silencing

Abstract: Apple latent spherical virus (ALSV) is an efficient virus-induced gene silencing vector in functional genomics analyses of a broad range of plant species. Here, an Agrobacterium-mediated inoculation (agroinoculation) system was developed for the ALSV vector, and virus-induced transcriptional gene silencing (VITGS) is described in plants infected with the ALSV vector. The cDNAs of ALSV RNA1 and RNA2 were inserted between the cauliflower mosaic virus 35S promoter and the NOS-T sequences in a binary vector pCAMBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
2
27
0
1
Order By: Relevance
“…The assumption that vsiRNA move throughout the plant to convey immunity still awaits direct experimental validation. Several studies have shown that antiviral acquired resistance can be passed transgenerationally to offspring through siRNAs and RdDM by the use of virus-induced TGS (VITGS) Kon and Yoshikawa, 2014; Martín-Hernández and Baulcombe, 2008; Otagaki et al, 2011). How VSR activities could modulate/interfere with resistance "priming" in subsequent generations is not known.…”
Section: Discussionmentioning
confidence: 98%
“…The assumption that vsiRNA move throughout the plant to convey immunity still awaits direct experimental validation. Several studies have shown that antiviral acquired resistance can be passed transgenerationally to offspring through siRNAs and RdDM by the use of virus-induced TGS (VITGS) Kon and Yoshikawa, 2014; Martín-Hernández and Baulcombe, 2008; Otagaki et al, 2011). How VSR activities could modulate/interfere with resistance "priming" in subsequent generations is not known.…”
Section: Discussionmentioning
confidence: 98%
“…It was not easy to insert exogenous nucleotide sequences into ALSV. After many trials (Li C et al, unpublished data), three cloning sites were successfully used for nucleotide insertions (Figure 2) [9,20]. One cloning site is located immediately after the stop codon of the polyprotein encoded by ALSV-RNA1 (named the SM site, after restriction sites for SalI and MluI; Figure 2A).…”
Section: Characteristics Of Alsv Vectormentioning
confidence: 99%
“…Such simultaneous expression/suppression of different genes is possible, but such vectors typically show low infection rates. The MN site was also used for virus-induced transcriptional gene silencing (VITGS) in N. benthamiana and petunia, where upstream sequences (promoters) of the target genes are methylated by virus vectors [20]. The nucleotide sequence of an apple gene promoter was also mutated and inserted at the XSB site for infection to apple plants [15].…”
Section: Characteristics Of Alsv Vectormentioning
confidence: 99%
“…These vectors had to be inoculated to Chenopodium quinoa plants for virus propagation [42]. Currently, we constructed RNA1 and RNA2 vectors using Ti plasmid where cloning sites for foreign gene were introduced in both RNA vectors [43,44]. As shown in Figure 1a, RNA1 vector has a cloning site in the 3′-noncoding region (SM), and RNA2 vector has two cloning sites in the ORF (XSB) and the 3′-noncoding region (MN).…”
Section: Apple Latent Spherical Virus (Alsv) Vectorsmentioning
confidence: 99%
“…As shown in Figure 1a, RNA1 vector has a cloning site in the 3′-noncoding region (SM), and RNA2 vector has two cloning sites in the ORF (XSB) and the 3′-noncoding region (MN). These vectors can be inoculated to Nicotiana benthamiana by agro-infiltration [43,44].…”
Section: Apple Latent Spherical Virus (Alsv) Vectorsmentioning
confidence: 99%